2013
DOI: 10.1073/pnas.1310631110
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHROME-DEPENDENT LATE-FLOWERING accelerates flowering through physical interactions with phytochrome B and CONSTANS

Abstract: In flowering plants, light is one of the major environmental stimuli that determine the timing of the transition from the vegetative to reproductive phase. In Arabidopsis, phytochrome B (phyB); phyA; cryptochrome 2; and FLAVIN-BINDING, KELCH REPEAT, F-BOX 1 are major photoreceptors that regulate flowering. Unlike phyA; cryptochrome 2; and FLAVIN-BINDING, KELCH REPEAT, F-BOX 1, phyB delays flowering mainly by destabilizing the CONSTANS (CO) protein, whose reduction leads to decreased expression of a florigen ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 50 publications
3
76
0
1
Order By: Relevance
“…As previously described, phyB mutant plants grown under continuous RL displayed a conspicuous early flowering phenotype (Reed et al, 1993;Endo et al, 2013), indicating that this wavelength delays flowering time in Arabidopsis. We have also grown Col, hos1, and the double hos1 phyB mutant under continuous RL, and we observed that hos1 flowering time is not as delayed as in the wild type, but later than in the phyB mutant ( Figure 3A).…”
Section: Mutations In Hos1 Affect Several Developmental Processes Regsupporting
confidence: 70%
See 2 more Smart Citations
“…As previously described, phyB mutant plants grown under continuous RL displayed a conspicuous early flowering phenotype (Reed et al, 1993;Endo et al, 2013), indicating that this wavelength delays flowering time in Arabidopsis. We have also grown Col, hos1, and the double hos1 phyB mutant under continuous RL, and we observed that hos1 flowering time is not as delayed as in the wild type, but later than in the phyB mutant ( Figure 3A).…”
Section: Mutations In Hos1 Affect Several Developmental Processes Regsupporting
confidence: 70%
“…In addition, several factors have been shown to interact with phyB and regulate photoperiodic flowering. The PHYTOCHROME-DEPENDENT LATE FLOWERING (PHL) nuclear protein accelerates flowering by suppressing the inhibitory effect of phyB on flowering time (Endo et al, 2013). PHL interacts physically with phyB in a RL-dependent manner and, in the presence of active phyB, PHL interacts with CO as well (Endo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PhyB-dependent regulation of CO stability can be explained by two distinct mechanisms [i.e. HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENE1 (HOS1) and PHYTOCHROME-DEPENDENT LATE-FLOWERING (PHL)] (Endo et al, 2013;Lazaro et al, 2015). In the morning, HOS1 E3 ubiquitin ligase restricts accumulation of CO protein by degrading it (Lazaro et al, 2012(Lazaro et al, , 2015.…”
Section: Posttranslational Regulation Of Co Proteinmentioning
confidence: 99%
“…In addition, HOS1 physically interacts with phyB and CO. PhyB-dependent CO destabilization can therefore operate through HOS1 in the morning. PhyB-dependent destabilization of CO can be relieved in the afternoon by PHL (Endo et al, 2013). In the afternoon, PHL functions as a positive regulator of flowering by countering the inhibitory effect of phyB on CO stability.…”
Section: Posttranslational Regulation Of Co Proteinmentioning
confidence: 99%